IMPLEMENTATION OF HUMAN RIGHTS IN EDUCATION: REFLECTIONS ON 80 YEARS OF INDONESIAN INDEPENDENCE AT MADRASAH ALIYAH NEGERI 1 SAMARINDA - Reza Alfiannur; Wingkolatin; Moh Bahzar; Endang Herliah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Education is one of the fundamental human rights for all people. With education, a person's life can change. This will be realised if everyone has the same opportunity to obtain an education. In the 80 years since Indonesia's independence, the country has implemented various education policies aimed at promoting human rights and social justice. This study focuses on analysing and reflecting on the implementation of human rights in education at Madrasah Aliyah Negeri 1 Samarinda. The aim is to contribute to the development of a fair and equitable society in the city of Samarinda. The research method used is qualitative, namely observation, interviews and documentation. The results of the study show that Madrasah Aliyah Negeri 1 Samarinda has ensured that students have equal opportunities to obtain their human rights in education, even though the school also has shortcomings.